A Research of Transition Metal Ions Doped Using Sodium Borate Glass: Exploring the Potential Applications and Optimization of Optical Properties (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Borate glasses are the technologically important class of glasses and play a significant role in various applications. A host of borate rich glasses containing alkali and alkaline earth fluorides as glass modifiers are optimistic materials for their probable applications in the field of optical communications, laser hosts, optical filters, photonic devices, and so forth. For many years, glasses containing transition metal ions have attracted attention because of their potential applications in electrochemical, electronic and electro-optic devices. Optimization of optical properties of glasses is a very important task prior to their application for optical devices. Optical spectroscopy is an important and mandatory tool for understanding the structure and dynamics of glassy amorphous materials.